Physiological and pathophysiological aspects of short-term middle-altitude adaptation in humans - A. R. Kiselev; N. A. Arablinsky; S. A. Mironov; M. A. Umetov; S. A. Berns; I. S. Yavelov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
The review presents up-to-date information on the physiological and pathophysiological aspects of short-term middle-altitude adaptation in healthy individuals and patients with various chronic diseases. Unlike acute mountain sickness, which develops going to ≥3000, the physiological aspects of human adaptation to 2000-2500 m remain insufficiently studied. However, these altitudes are the most visited among tourist groups and individually.